Role of substance P and the neurokinin 1 receptor in acute pancreatitis and pancreatitis-associated lung injury - Bhatia, Madhav (The National Academy of Sciences, 1998)
Substance P, acting via the neurokinin 1 receptor (NK1R), plays an important role in mediating a variety of inflammatory processes. However, its role in acute pancreatitis has not been previously described. We have found that, in normal mice, substance P levels in the pancreas and pancreatic acinar cell expression of NK1R are both increased during secretagogue-induced experimental pancreatitis. To evaluate the role of substance P, pancreatitis was induced in mice that genetically lack NK1R by administration of 12 hourly injections of a supramaximally stimulating dose of the secretagogue caerulein. During pancreatitis, the magnitude of hyperamylasemia, hyperlipasemia, neutrophil sequestration in the pancreas, and pancreatic acinar cell necrosis were significantly reduced in NK1R−/− mice when compared with wild-type NK1R+/+ animals. Similarly, pancreatitis-associated lung injury, as characterized by intrapulmonary sequestration of neutrophils and increased pulmonary microvascular permeability, was reduced in NK1R−/− animals. These effects of NK1R deletion indicate that substance P, acting via NK1R, plays an important proinflammatory role in regulating the severity of acute pancreatitis and pancreatitis-associated lung injury.